Asesmen Tingkat Potensi Bahaya dan Fasilitas Keselamatan Kerja di Laboratorium Pendidikan: Assessment of Potential Hazard Levels and Occupational Safety Facilities in Educational Laboratories - Daryono, Retno Novvitasari Hery (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Workplace safety in laboratories is a top priority, especially for activities involving materials that have the potential to pose hazards, such as flammable chemicals or substances that may cause health issues. Educational laboratories in higher education institutions carry such hazard potential, necessitating adequate safety facilities and work safety procedures. This study aims to assess the level of hazard potential, as well as the implementation of work safety measures and the availability of safety facilities in educational laboratories at the university level. Data collection methods include questionnaires and interviews. The results indicate that most educational laboratories have a low level of dangerous gases, toxic chemicals, corrosive chemicals, and flammable chemical hazard potential. This hazard potential is supported by essential safety facilities such as fume hoods and fire extinguishers. This finding suggests that the availability of supporting safety facilities needs to be installed to improve the laboratory safety.